Introduction to molecular thermodynamics - Hanson, Robert M. (Intergrated Graphics Northfield, 1999)
Takes readers on an adventure into the inner workings of the molecular world, following a step-by-step progression of ideas and examples from the field. This volume features helpful pedagogy, including chapter ending-summaries, problems and brain teasers, with answers.